Showdown at the 1964 Democratic Convention Lyndon Johnson, Mississippi and civil rights - Skipper, John C., 1945- (McFarland & Co., Publishers, 2012)
"This volume explores how American politics and the civil rights movement faced head-to-head at the 1964 Democratic National Convention in Atlantic City, New Jersey, how the federal government felt compelled to spy on its own people for purely political purposes, and how this interlude changed the political landscape for generations"--Provided by publisher.